Awakening of Soul Consciousness by the Breakthrough Experiences of Life: An Approach to the Reconstruction of Reality - Gillani, Iram; Shaheen, Razia; Ferdoos, Amber (Al-Irfan, 2021)
This qualitative research intended to explore with a thematic analysis the role of breakthrough experiences of life that cause the deep awakening of the soul consciousness. With the purposive sampling, a homogeneous group of 10 respondents was selected from multi religions (Muslim, Christian, Zen, Buddhist, Non-dual, Hinduism) belonging to diverse cultural, ethnic, and educational backgrounds. They were identified through their recognized work that was, directly and indirectly, addressing the soul consciousness and sharing their spiritual transformation. Participants belonged to different countries including Pakistan, Lebanon, England, the USA, Norway, India, Canada, and Germany. The in-depth interviews were followed by the thematic analysis to unfold the concealed patterns and connections of their breakthrough experiences to discover the hidden meanings. The most highlighted breakthroughs that cause the awakening of the soul consciousness included loss of the loved one, near death experience (NED), prolonged illness, trauma, love, divorce, and a series of sacred dreams. Resultantly, the prevalent traits of the soul consciousness after the awakening were, deep relationship with God and nature, acceptance of Divine Will, sense of being connected with all, acquisition of wisdom, discovering the purpose of life, altruistic behavior, gratitude, pure intuitive awareness, profound inner peace and serving humanity. This research paper offers a unique paradigm for the reconceptualization of perceiving and describing breakthrough experiences of life. This study explored breakthrough experiences of varying nature as greatly productive and constructive yet challenging aspects of inner developmental processes and spiritual transformation.